1997
DOI: 10.1074/jbc.272.26.16618
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution in Vitro of the V1 Complex from the Yeast Vacuolar Proton-translocating ATPase

Abstract: Oligomeric assembly is a fundamental aspect of many complex enzymes. Using our native gel technique for examining subcomplexes of the V-ATPase V 1 sector, we have developed an in vitro reconstitution assay for assembly of this complex. Assembly of complex II, the soluble V 1 complex observed in native gels, is dependent upon the presence of divalent cations and physiological temperatures. Assembly of soluble V 1 can occur in a stepwise fashion from smaller subcomplexes found in some strains deleted for V-ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 24 publications
4
40
1
Order By: Relevance
“…However, the molecular mass of the cross-linked product (46 kDa) together with the fact that it does not react with the anti-F subunit antibody makes it likely that it does reflect a contact between subunits E and G. These observations are consistent with previous findings that a subcomplex containing at least subunits E and G as well as a subcomplex containing at least subunits D and F could be isolated from a variety of yeast strains deleted in various vma genes (42,43), and demonstrate that these contacts are preserved in both the V 1 V 0 and V 1 complexes.…”
Section: Discussionsupporting
confidence: 82%
“…However, the molecular mass of the cross-linked product (46 kDa) together with the fact that it does not react with the anti-F subunit antibody makes it likely that it does reflect a contact between subunits E and G. These observations are consistent with previous findings that a subcomplex containing at least subunits E and G as well as a subcomplex containing at least subunits D and F could be isolated from a variety of yeast strains deleted in various vma genes (42,43), and demonstrate that these contacts are preserved in both the V 1 V 0 and V 1 complexes.…”
Section: Discussionsupporting
confidence: 82%
“…Early data obtained from yeast two-and three-hybrid experiments and native subcomplex isolation in subunit deficient mutant strains, as well as co-immunoprecipitation, have helped identify important interactions between the different subunits of yeast V-ATPase (16,38,48,49). In addition, neighboring subunits have been identified by chemical cross-linking experiments (17,19) in native complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have already indicated that these subunits might interact (16,17,38). However, very few data exist on the isolated subunits.…”
Section: Expression and Purification Of The Recombinant Subunits-mentioning
confidence: 99%
“…The E subunit is not the main catalytic subunit of V-ATPase, but it was reported that the E subunit was essential for ATP hydrolysis (4) and might neighbor the A 3 B 3 complex of the main catalytic domain (12). The exact position of the E subunit in the tertiary structure of V-ATPase and the role of the subunit in enzymatic function remain to be clarified.…”
Section: Table I Comparison Of the Compositions Of D And E Subunits Imentioning
confidence: 99%
“…The rotation of the ␥ subunit is thought to be physicochemically coupled with H ϩ translocation in the F 0 domain (membrane domain). In V-ATPase, the homologue of the ␥ subunit has not yet been identified, although some candidates have been recommended, such as the D subunit (11) or a pair of D and E subunits (12). On the other hand, Xie reported that at least the A, B, C, E, and G subunits, but not the D or F subunits, were essential for ATP hydrolysis (4).…”
mentioning
confidence: 99%